Convalescent plasma therapy for the treatment of patients with COVID‐19: Assessment of methods available for antibody detection and their correlation with neutralising antibody levels - Harvala, H; Robb, ML; Watkins, N; Ijaz, S; Dicks, S; Patel, M; Supasa, P; Wanwisa, D; Liu, C; Mongkolsapaya, J; Bown, A; Bailey, D; et al. (Wiley, 2020)
Introduction: The lack of approved specific therapeutic agents to treat coronavirus disease (COVID‐19) associated with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection has led to the rapid implementation of convalescent plasma therapy (CPT) trials in many countries, including the United Kingdom. Effective CPT is likely to require high titres of neutralising antibody (nAb) in convalescent donations. Understanding the relationship between functional neutralising antibodies and antibody levels to specific SARS‐CoV‐2 proteins in scalable assays will be crucial for the success of a large‐scale collection. We assessed whether neutralising antibody titres correlated with reactivity in a range of enzyme‐linked immunosorbent assays (ELISA) targeting the spike (S) protein, the main target for human immune response.